2019
DOI: 10.1016/j.devcel.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Mediated Cholesterol Trafficking Controls Steroid Production

Abstract: Highlights d Autophagy regulates steroid production d Autophagosomes sequester and traffic cholesterol substrate for steroid production d The Warts effector microRNA bantam regulates autophagy via the EcR and Tor pathways d Autophagy-dependent steroid regulation adjusts growth to nutrient availability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 63 publications
0
58
1
Order By: Relevance
“…In addition, the potential function of V‐ATPase in the autophagic process could regulate trafficking of cholesterol, a common precursor steroid, directly impacting ecdysone production. Indeed, loss of the autophagic pathway decreases ecdysone biosynthesis with a concomitant overgrowth of larvae 62 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the potential function of V‐ATPase in the autophagic process could regulate trafficking of cholesterol, a common precursor steroid, directly impacting ecdysone production. Indeed, loss of the autophagic pathway decreases ecdysone biosynthesis with a concomitant overgrowth of larvae 62 …”
Section: Discussionmentioning
confidence: 99%
“…Warts (LATS1/2 in mammals) regulate steroid hormone production through an autophagydependent pathway (also called lipophagy). Precisely, Warts control the production of Drosophila steroid ecdysone through their effector microRNA bantam, which responds to nutrients, thus mobilizing the transport of the steroid precursor cholesterol 37 . Notably, YAP (mammalian Yki homolog) regulates steroidogenesis in tumor cells 38 , indicating that the regulation of steroidogenesis by the Wts-Yki pathway may be an evolutionarily conserved mechanism.…”
Section: Crosstalk Between the Hippo Pathway And Autophagy In Drosophilamentioning
confidence: 99%
“…DR also induces autophagy and it is essential for extending lifespan [64]. At present, pathways related to autophagy are PI3K/Akt, EcR and mTOR [65,66]. In this study, many DEPs were not only found in the PI3K/Akt and mTOR pathways, but also involved in lysosomes according to the GO enrichments and KEGG pathway annotations, which provided clues for further research on the mechanism of DR induced autophagy.…”
Section: Autophagy Related Pathways Were Annotated During Drmentioning
confidence: 52%